2011
DOI: 10.1530/eje-10-1063
|View full text |Cite
|
Sign up to set email alerts
|

Elevated LH predicts ischaemic heart disease events in older men: the Health in Men Study

Abstract: Context: Hypogonadism in men is associated with insulin resistance, elevations in pro-inflammatory cytokines and fibrinogen, and an atherogenic lipid profile. However, it is uncertain whether the age-related decline in testosterone is associated with ischaemic heart disease (IHD) events. Objective: To determine whether testosterone and its associated hormones, sex hormone-binding globulin (SHBG) and LH, predict IHD events in older men. Design: Prospective cohort study. Methods: Between 2001 and 2004, 3637 comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…From a clinical perspective, we should ponder whether low TT might be related to cardiovascular disease via effects on serum lipid levels. In addition, evidence has shown that high luteinizing hormone (LH) level is related to the CHD risk or is involved in arterial dilatation as well as occlusive vascular disease in older men (46,47,48,49). LH might have an independent effect on the cardiovascular system via the LH receptor or rather be an epiphenomenon of another disease process.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, we should ponder whether low TT might be related to cardiovascular disease via effects on serum lipid levels. In addition, evidence has shown that high luteinizing hormone (LH) level is related to the CHD risk or is involved in arterial dilatation as well as occlusive vascular disease in older men (46,47,48,49). LH might have an independent effect on the cardiovascular system via the LH receptor or rather be an epiphenomenon of another disease process.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that men with elevated LH were more likely to experience ischemic heart disease (IHD) events (21). To explore whether this association was also present with regard to CVD mortality, we stratified men by gonadal status using established Australian consensus guidelines (29).…”
Section: Cardiovascular Mortality By Hypogonadism Categoriesmentioning
confidence: 99%
“…The ability to draw conclusions from the data is further limited by differences in age range, definition of endpoints, and in the few studies examining causespecific mortality, failure to control for the problem of competing risks. Additionally, as far as we are aware, no previous study has examined the relationship between mortality and gonadotropins, which together with testosterone, may provide better risk stratification than testosterone levels alone (21).…”
mentioning
confidence: 99%
“…Contrary to the widespread belief that T is related to a higher cardiovascular risk, studies show that atherosclerosis is mostly related to low T levels 7177. Moreover, direct antianginal effects have been described with T administration 78,79.…”
Section: Testosteronementioning
confidence: 85%